Co‐constructing an Interactive Tool to Support Climate Change Resilience Planning in Industry - Sydney Sroka; Leela Velautham; Abigail Idiculla (Climate Resilience and Sustainability)
ABSTRACT Comprehensive resilience planning and resilience‐centered decision making at large, multinational companies is complex and not currently well‐served by publicly available tools. Over the course of a year, researchers collaborated with US‐based professionals from 14 global companies representing many different industries through a mixture of focus groups and individual meetings to co‐construct a resilience tool that would serve their common resilience planning needs. This interactive geospatial map of the United States visualized and made interoperable publicly accessible data sets relevant to the physical and transition risks of climate change. At the end of the development process, semistructured interviews were conducted with industry professionals about the state of US‐based industrial resilience planning in their respective companies and specific ways in which the tool could be used and further developed to assist such work. In this paper, we present a prototype of the tool and an overview of its development process. Through analysis of the tool's development and the post‐development interviews, we additionally outline some considerations shaping resilience planning at large, multinational organizations, as well as explore the benefits of coproduction between research and industry for addressing complex, interdisciplinary problems such as climate change.